Primary pure spindle cell carcinoma (sarcomatoid carcinoma) of the ovary: A case report with immunohistochemical study. Issue 1 (December 2016) - Giordano, Giovanna; Berretta, Roberto; Silini, Enrico
Abstract Background In the ovary, sarcomatoid carcinoma has been reported only as mural nodules in epithelial malignant or borderline serous or mucinous cystic neoplasms, and in teratomas. In this paper we report a rare case of a solid sarcomatoid carcinoma of the ovary, without accompanying component of giant cells, pleomorphic cells, or glandular and other epithelial structures. Case presentation This case report refers to a sarcomatoid carcinoma of the ovary in in a 57 year-old woman with abdominal pain. Macroscopically, the neoplasm was a 15x10x5 cm ovarian mass that featured gray white solid fleshy areas, interspersed with areas of necrosis, hemorrhage and cystic spaces filled with thick fluid. The epithelial differentiation of the tumor was demonstrated by strong and diffuse reactivity to CAM5.2 and focal immunoreactivity to EMA. A diagnosis of malignant mesenchymal tumor was excluded due to negativity for desmin, smooth muscle actin, caldesmon, CD34, CD10, and myoglobin. Neural, neuroendocrine neoplasm, melanoma and Perivascular Epithelioid Cell Tumor (PEComa) were excluded because of negativity for S100, chromogranin, synaptophysin and HMB45. Conclusion Primary ovarian spindle cell carcinoma is a rare neoplasm, which must be considered in the differential diagnosis of solid ovarian mass with spindle cell appearance. This case adds to our knowledge of the biological behavior of these rare neoplasms. The distinction from true sarcomas and carcinosarcomas is important because of the more favorable prognosis of the spindle cell carcinomas. However their diagnosis necessitates a careful tissue sampling and immunohistochemical staining.